A New Strategy to Inhibit Scar Formation by Accelerating Normal Healing Using Silicate Bioactive Materials - Zhaowenbin Zhang; Chen Fan; Qing Xu; Feng Guo; Wenbo Li; Zhen Zeng; Yuze Xu; Jing Yu; Hongping Ge; Chen Yang; Jiang Chang (Advanced Science)
Abstract Inspired by the scar‐free wound healing in infants, an anti‐scar strategy is proposed by accelerating wound healing using silicate bioactive materials. Bioglass/alginate composite hydrogels are applied, which significantly inhibit scar formation in rabbit ear scar models. The underlining mechanisms include stimulation of Integrin Subunit Alpha 2 expression in dermal fibroblasts to accelerate wound healing, and induction of apoptosis of hypertrophic scar fibroblasts by directly stimulating the N‐Acylsphingosine Amidohydrolase 2 expression in hypertrophic scar fibroblasts, and indirectly upregulating the secretion of Cathepsin K in dermal fibroblasts. Considering specific functions of the bioactive silicate materials, two scar treatment regimes are tested. For severe scars, a regenerative intervention is applied by surgical removal of the scar followed by the treatment with bioactive hydrogels to reduce the formation of scars by activating dermal fibroblasts. For mild scars, the bioactive dressing is applied on the formed scar and reduces scar by inducing scar fibroblasts apoptosis.